Modern Classic Home Design with Multimedia-Based AutoCAD and SketchUp: Dinur Syahputra, Aripin Rambe, Dewi Wahyuni - dinur syahputra; Aripin Rambe; Dewi Wahyuni (Bahasa Indonesia, 2023)
Design is the process of planning and designing an object with the aim that the object has a function, aesthetic value and is useful for humans. Design involves the creative process of designing something so as to create something functional for its users. Multimedia is the use of computers to present and combine text, sound, images, animation, audio and video with tools. In multimedia there are many fields and types that can be studied. There is such a thing as graphic design, videography, photography, animation and so on. In this case the author is working on "Classic Modern Home Design with Multimedia-Based AutoCAD and SketchUp.